Capability of Quasar Selection by Combining SCUSS and SDSS Observations. (4th January 2016) - Zou, Hu; Wu, Xue-bing; Zhou, Xu; Wang, Shu; Jiang, Linhua; Fan, Xiaohui; Fan, Zhou; Jiang, Zhaoji; Jing, Yipeng; Lesser, Michael; Li, Cheng; Ma, Jun; et al.
Abstract: The South Galactic Cap u -band Sky Survey (SCUSS) provides a deep u -band imaging of about 5000 deg 2 in south Galactic cap. It is about 1.5 mag deeper than the SDSS u -band. In this article, we evaluate the capability of quasar selection using both SCUSS and SDSS data, based on considerations of the deep SCUSS u -band imaging and two-epoch u -band variability. We find that the combination of the SCUSS u -band and the SDSS griz -band allows us to select more faint quasars and more quasars at redshift around 2.2 than the selection that uses only the SDSS ugriz data. Quasars have significant u -band variabilities. The fraction of quasars with large two-epoch variability is much higher than that of stars. The selection by variability can select both low-redshift quasars with ultraviolet excess and mid-redshift (2 <  z  < 3.5) quasars where quasar selection by optical colors is inefficient. The above two selections are complementary and make full use of the SCUSS u -band advantages.